Small Powers and Trading Security - Magcamit, Michael Intal. author. aut Link
XXI, 269 p. 4 illus.
Keywords: This book examines why and how small powers link their security interests and trade agendas, and how security threats influence the facilitation and outcome of their trade activities. In doing so, it analyses the increasingly complex connections between trade and security, demonstrating how these linkages affect the overall security of four small but important states in East Asia. Focusing on the role of high levels of internal and external insecurities, marginal geo-economic size and peripheral geopolitical position, and multidimensional and multidirectional security contexts and threats, the author concludes that for every security enhancement that a linkage creates a consequent security risk is generated. In other words, Taiwan, Singapore, Malaysia, and the Philippines are effectively trading their security. This innovative book will appeal to political scientists, economists, and security and trade experts.